Strategic Management in Achieving the School Vision and Mission: A Case Study of SMPN 32 Banjarmasin, South Kalimantan - Raihanah Raihanah; Rahmi Widyanti; Mohammad Zainul (Jurnal Multidisiplin Sahombu, 2026)
This study examines how SMPN 32 Banjarmasin implements strategic management to achieve its school vision and mission. The school’s vision emphasizes three core ideals: excellence in achievement, noble character, and environmentally conscious cultural values. Using a qualitative case study design, the research explored how strategic planning was formulated, how programs were implemented and supervised, what obstacles emerged during implementation, what efforts were taken to address these obstacles, and which internal and external factors influenced the effectiveness of the strategy. Data were collected from 13 purposively selected informants, including the principal, vice principals, teachers, administrative staff, a student, and a school committee representative. The data collection techniques included in-depth interviews, participatory observation, and documentation, and the data were analyzed through reduction, display, and verification. The findings show that the school applied an integrated strategic management process consisting of needs-based planning, clear organizational structuring, continuous direction, and tiered supervision. The major obstacles included uneven teacher competence in digital learning, limited facilities, inconsistencies in coordination and evaluation, student discipline issues, low parental participation, restricted funding, and uneven technology adaptation. In response, the school strengthened internal collaboration, conducted training, improved resource allocation, expanded external partnerships, and reinforced digital literacy for teachers and students. The study concludes that the achievement of school vision and mission requires continuous, adaptive, and collaborative strategic management supported by visionary leadership, school culture, stakeholder participation, and adequate facilities.